Characterization of starch branching enzyme I (SBE I) gene in two Triticum monococcum accessions with different starch content. Issue 7 (7th May 2015) - Wang, Xiu‐Ying; Ma, Jian; Wang, Chang‐Shui; Zhang, Ling‐Ling; Wang, Ji‐Rui; Liu, Ya‐Xi; Qi, Peng‐Fei; Wei, Yu‐Ming; Zheng, You‐Liang; Jiang, Qian‐Tao
<x xml:space="preserve">Abstract</x> Starch‐branching enzyme I (SBE I) belongs to a member of SBEs isoforms, which plays an important role in amylopectin biosynthesis. In this study, we measured starch content, determined SBE activity within endosperms, analyzed expression patterns of SBE I by real‐time quantitative PCR(RT‐qPCR), and characterized sequences of SBE I from two accessions (Y59 and Y63) of Triticum monococcum with different starch content. Our results indicated that contents of total starch and amylopectin during grain development were significantly different between the two investigated accessions. Analysis of enzyme activity revealed that SBE activity in endosperm of Y59 was obviously higher than that in Y63 at early developmental stage. Accumulation rates of both amylopectin and starch were significantly correlated to the SBE activities in the two accessions. Expression analysis showed that SBE I genes were highly expressed at middle stage of development. Further, the expression of SBE I in Y59 was higher than that in Y63 from 5 days after pollination (DAP) to 23 DAP. Coding sequences of SBEI in both Y59 and Y63 included a 2490‐bp opening reading frame (ORF) encoding 829 amino acids. The genomic DNAs of SBE I were about 5.5 kb in length, contained 14 exons and 13 introns, and shared a similar structure with wheat. Our results may provide some bases to research amylopectin accumulation of T. monococcum, further provided relevant theoretical foundation for exploring the amylopectin synthesis in wheat.